2020
DOI: 10.1029/2020gl091208
|View full text |Cite
|
Sign up to set email alerts
|

Uplift Mechanism of the Highest Mountains at Eastern Himalayan Syntaxis Revealed by In Situ Dense Gravimetry

Abstract: Dense gravity surveys at 408 stations are built around eastern Himalayan syntaxis (EHS). Free-air gravity anomalies (FGAs) and Bouguer gravity anomalies (BGAs) are obtained based on the in situ data, while the modeled and observed FGAs are merged to increase the accuracy of the gravity anomalies. The variation ranges of FGAs and BGAs are −350-100 and −520 to −320 mGal, respectively. The density structures inversed by the BGAs represent a low-density zone below the Namche Barwa-Gyala Peri metamorphic massif. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Gravity data have been widely used to study the crustal structure beneath the Tibetan Plateau, especially the Moho relief (e.g., Xu et al., 2017; Zhao et al., 2020). However, only a few studies are reported about the upper mantle structure inferred from gravity data (e.g., Ravikumar et al., 2020; She & Fu, 2020). We use our inversion method and the EIGEN‐6C4 gravity data to obtain the mantle density variations beneath the Tibetan Plateau.…”
Section: Application To the Tibetan Plateaumentioning
confidence: 99%
“…Gravity data have been widely used to study the crustal structure beneath the Tibetan Plateau, especially the Moho relief (e.g., Xu et al., 2017; Zhao et al., 2020). However, only a few studies are reported about the upper mantle structure inferred from gravity data (e.g., Ravikumar et al., 2020; She & Fu, 2020). We use our inversion method and the EIGEN‐6C4 gravity data to obtain the mantle density variations beneath the Tibetan Plateau.…”
Section: Application To the Tibetan Plateaumentioning
confidence: 99%
“…We adopt the multi‐source data joint inversion method (She & Fu, 2020, see Supporting Information) to invert the crustal structure along the profile. We construct the initial model based on S‐wave velocity tomography results (Li et al, 2002, 2012; Zhao et al, 2003).…”
Section: Data Gravity Anomaly and Crustal Structurementioning
confidence: 99%
“…The crustal density structure of the profiles was inversed by using the Gravity/Magnetic Model Software provided from Northwest Geophysical Associates with BGAs data as input (Figure 3). The detailed calculation method is the same as described in Supporting Information S1 of She and Fu (2020). Our initial crustal density model is based on the S wave velocity structure in this region obtained from the combined surface wave dispersion and receiver functions of Zheng et al (2016).…”
Section: Moho Changes and Density Structures In Western Yunnanmentioning
confidence: 99%